ربطِ آیات وسور اور اس کی اہمیت: مسلم اہلِ علم کی آرا کا مطالعہ: Coherence in Qur̓ānic Verses and Sūrās and its Importance: A Study of the Views of Islamic Scholars (Al-Qamar, 2020)
This paper studies the importance of coherence in the verses and Sūrās of the Quran in the light of different scholars’ views. It maintains that the Holy Quran is divided into verses and Sūrās according to its order, which have been revealed in small parts over a period of twenty-three years. In addition to the different order of revelation, these parts have been compiled in a special order under the guidance of the Prophet Muhammad. The inevitable result is that this sequence is not a coincidence but a coherent and proportional one. Scholars interpret this interrelationship with the word Rabt. Literal and terminological meanings of Rabt is connection and its importance in the field of Qur̓ānic interpretation have been discussed in this paper.
Keywords: Quran; Verses; Coherence; Islamic Scholars